Reversal Circularly Polarized Luminescence of AIE-Active Chiral Binaphthyl Molecules from Solution to Aggregation - Sheng, Yuan; Shen, Dong; Zhang, Wenjie; Zhang, Hongxing; Zhu, Chengjian; Cheng, Yixiang (Chemistry : a European journal, 2015)
Four aggregation‐induced emission (AIE)‐active chiral binaphthyl‐based molecules, (R/S)‐1 and (R/S)‐2, were designed and synthesized. Interestingly, all of them can exhibit reversal circularly polarized luminescence (CPL) signals from solution to aggregation, which could be attributed to the different dihedral angle of binaphthyl units from cis‐conformation in pure THF solution to trans‐conformation in THF/water mixtures. The closing scene: Four aggregation‐ induced emission (AIE)‐active chiral binaphthyl‐based molecules, (R/S)‐1 and (R/S)‐2, were designed and synthesized. Interestingly, all of them can exhibit reversal circularly polarized luminescence (CPL) signals from solution to aggregation, which could be attributed to the different dihedral angle of binaphthyl units from cis‐conformation in pure THF solution to trans‐conformation in THF/water mixtures.